The effect of total sulfated glycosaminoglycans from crown-of-thorns acanthaster planci on wound healing - Bahrom, Nur Afiqah (2016)
Coral reef deforestation by corallivore crown-of-thorns (COTS) Acanthaster planci could result into a hazardous effect towards the quantity and quality of the majestic coral reefs. Effort should be made to generate wealth from COTS, a material that does not have any commercial value, such as studies to identify the therapeutic potentials from the COT. This study investigate the occurrence of total sulfated GAGs from the integument, internal tissue and coelomic fluid of COTS starfish and evaluate the effect of total sulfated GAGs on wound healing in rats using macroscopic and microscopic evaluations. The integument and coelomic fluid from body region were the highest source of total and N-sulfated GAGs. There was more N-sulfated GAGs compared to O-sulfated GAGs for percentage (%) division in both regions. This finding suggested heparin and/or heparin sulphate, the only species of GAGs that have N-sulfated group in its disaccharide chain, could be found in body region of COTS, particularly integument and coelomic fluid parts. 20 μl of 1 μg/ml concentration of total sulfated GAG from each anatomical part of each COTS region were applied to the full-thickness excisional wound model from Day 0 to Day 12, with PBS application as control group. The progress of healing was assessed through macroscopic examination and analysis of epithelization, inflammatory cells, fibroblasts proliferation, new vessels formation andcollagen fibers organisation using light microscope (LM), transmission electron microscope (TEM) and scanning electron microscope (SEM). Macroscopic examination revealed significant (p<0.0167) wound contraction percentage (%) on each observation (Day 1, Day 6 and Day 12) and epithelization progress occurred in all sulfated GAGs treated group from COTS’ body region as compared to control group. LM and SEM evaluations showed that all treatment groups have fully bridged the excised wound on the 12th day of observations. LM and TEM evaluations showed enhanced fibroblasts proliferation with significant (p<0.0167) finding occurred in all sulfated GAGs treated group from COTS’ body region and integument of arm region compared to control group. For new vessels formation, LM and TEM analysis showed a significant (p<0.0167) increase in the sulfated GAGs treated group from integument of body region (2.00, IqR 0.17) and integument of arm region (2.02, IqR 0.11) as compared to control group. LM, TEM and SEM evaluations showed that sulfated GAGs from all anatomical parts of both COTS’ regions stimulate dense organisation of collagen fibers on the 12th day of observation, significantly (p<0.0167) compared to control group. This study strongly indicate that sulfated GAGs in particularly from its integument and coelomic fluid of COTS’ body region, seems to hasten the wound healing event through positive effect on acceleration of wound contraction percentage (%), enhance epithelization migration, fibroblast proliferation, angiogenesis process and collagen organization